SCF(FBXW7)-mediated degradation of p53 promotes cell recovery after UV-induced DNA damage - Galindo-Moreno, María (FASEB J, 2019)
Eukaryotic cells have developed sophisticated mechanisms to ensure the integrity of the genome and prevent the transmission of altered genetic information to daughter cells. If this control system fails, accumulation of mutations would increase risk of diseases such as cancer. Ubiquitylation, an essential process for protein degradation and signal transduction, is critical for ensuring genome integrity as well as almost all cellular functions. Here, we investigated the role of the SKP1–Cullin-1–F-box protein (SCF)-[F-box and tryptophan-aspartic acid (WD) repeat domain containing 7 (FBXW7)] ubiquitin ligase in cell proliferation by searching for targets implicated in this process. We identified a hitherto-unknown FBXW7-interacting protein, p53, which is phosphorylated by glycogen synthase kinase 3 at serine 33 and then ubiquitylated by SCF(FBXW7) and degraded. This ubiquitylation is carried out in normally growing cells but primarily after DNA damage. Specifically, we found that SCF(FBXW7)-specific targeting of p53 is crucial for the recovery of cell proliferation after UV-induced DNA damage. Furthermore, we observed that amplification of FBXW7 in wild-type p53 tumors reduced the survival of patients with breast cancer. These results provide a rationale for using SCF(FBXW7) inhibitors in the treatment of this subset of tumors.—Galindo-Moreno, M., Giráldez, S., Limón-Mortés, M. C., Belmonte-Fernández, A., Reed, S. I., Sáez, C., Japón, M. Á., Tortolero, M., Romero, F. SCF(FBXW7)-mediated degradation of p53 promotes cell recovery after UV-induced DNA damage.